2016
DOI: 10.1016/j.advwatres.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Root-zone plant available water estimation using the SMOS-derived soil water index

Abstract: Currently, there are several space missions capable of measuring surface soil moisture, owing to the relevance of this variable in meteorology, hydrology and agriculture. However, the Plant Available Water (PAW), which in some fields of application could be more important than the soil moisture itself, cannot be directly measured by remote sensing. Considering the root zone as the first 50 cm of the soil, in this study, the PAW at 25 cm and 50 cm and integrated between 0 and 50 cm of soil depth was estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…They are based on the synergy of passive microwaves with ancillary optical visible/infrared (VIS/IR) [43,44] or active data [45]. Another approach allows assessment of plant available water at the 0-50 cm depth from the SMOS surface soil moisture based on the Soil Water Index (SWI) as a proxy of the root-zone soil moisture [22]. The SWI is also used as a proxy of drought [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are based on the synergy of passive microwaves with ancillary optical visible/infrared (VIS/IR) [43,44] or active data [45]. Another approach allows assessment of plant available water at the 0-50 cm depth from the SMOS surface soil moisture based on the Soil Water Index (SWI) as a proxy of the root-zone soil moisture [22]. The SWI is also used as a proxy of drought [23].…”
Section: Discussionmentioning
confidence: 99%
“…SMOS data supplements the CWB's information on soil moisture, which allows the indication of soil moisture conditions suitable for plant growth, and threats of droughts and floods. Comparisons of SMOS data against in-situ SM measurements showed good values of correlation (R > 0.7) [25,26] and relatively low RMSE (i.e., 0.04 m 3 m −3 ) [7,22,26].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As previously stated, the SMOS is only capable of retrieving the SM content of the soil top layer, which surely underestimates the root-zone SM. In the near future, the availability of root-zone SM estimates [92,93] is expected to improve the current estimation based on surface SM data for agricultural drought monitoring. Nevertheless, recent research has shown the capability of using satellite surface SM estimations for drought monitoring, e.g., using the surface SM observations from the Advanced Microwave Scanning Radiometer for Earth (AMSR-E) observation system and SMAP, after applying a cumulative distribution function (CDF) matching in situ surface SM data to remove the systematic bias and dynamic range differences [79,94].…”
Section: Drought Weeks Capturedmentioning
confidence: 99%
“…This region is mainly characterized by a large plain surrounded by mountains to the North, South and East. The extension of the plain is approximately 65 000 km 2 and has a mean altitude of 800 m. Its climate is continental semi-arid Mediterranean with a mean annual temperature of 11.8 • C. The Castilla y León region suffers of scarcity of water, with an average annual precipitation of 450 mm (González-Zamora et al, 2015). Despite this, it is one of the largest agricultural areas of the European Union, chiefly dedicated to rainfed agriculture.…”
Section: Study Areamentioning
confidence: 99%